Insulin Receptor Substrate-1 Associates with Small Nucleolar RNA Which Contributes to Ribosome Biogenesis - Ozoe, Atsufumi; Sone, Meri; Fukushima, Toshiaki; Kataoka, Naoyuki; Chida, Kazuhiro; Asano, Tomoichiro; Hakuno, Fumihiko; Takahashi, Shin-Ichiro (Frontiers in Endocrinology, 2014)
Insulin receptor substrates (IRSs) are well known to play crucial roles in mediating intracellular signals of insulin-like growth factors (IGFs)/insulin. Previously we showed that IRS-1 forms high molecular mass complexes containing RNAs. To identify RNAs in IRS-1 complexes, we performed UV cross-linking and immunoprecipitation (CLIP) analysis using HEK293 cells expressing FLAG-IRS-1 and FLAG-IRS-2. We detected the radioactive signals in the immunoprecipitates of FLAG-IRS-1 proportional to the UV irradiation, but not in the immunoprecipitates of FLAG-IRS-2, suggesting the direct contact of RNAs with IRS-1. RNAs cross-linked to IRS-1 were then amplified by RT-PCR, followed by sequence analysis. We isolated sequence tags attributed to 25 messenger RNAs and 8 non-coding RNAs, including small nucleolar RNAs (snoRNAs). We focused on the interaction of IRS-1 with U96A snoRNA (U96A) and its host Rack1 (receptor for activated C kinase 1) pre-mRNA. We confirmed the interaction of IRS-1 with U96A, and with RACK1 pre-mRNA by immunoprecipitation with IRS-1 followed by Northern blotting or RT-PCR analyses. Mature U96A in IRS-1-/- mouse embryonic fibroblasts was quantitatively less than WT. We also found that a part of nuclear IRS-1 is localized in the Cajal body, a nuclear subcompartment where snoRNA mature. The unanticipated function of IRS-1 in snoRNA biogenesis highlights the potential of RNA-associated IRS-1 complex to open a new line of investigation to dissect the novel mechanisms regulating IGFs/insulin-mediated biological events.